Bouguer and mantle gravity maps of Nigeria. Issue 27 (13th December 2022) - Apeh, Ojima Isaac; Tenzer, Robert; Kemgang Ghomsi, Franck Eitel; Rathnayake, Samurdhika
Abstract: We used global gravitational models together with topographic, bathymetric, and lithospheric density structure datasets to compile Bouguer and mantle gravity maps of Nigeria, and then used these gravity maps to interpret the crustal and upper mantle structure in this country. We applied methods for a spherical harmonic analysis and synthesis of gravitational and lithospheric density structure models to produce both gravity maps. Whereas existing Bouguer gravity datasets for different parts of Nigeria were computed by applying only a simple planar Bouguer gravity reduction and a planar terrain gravity correction, our approach took into consideration the Earth's spherical approximation and the spherical terrain correction, the ocean density contrast as well as density variations within sediments and the underlying consolidated crust. This study also provides the first mantle gravity map of Nigeria. Our results show that the free-air gravity pattern reflects mainly a topographic relief with prevailing positive values over topographically elevated regions, while Cretaceous sedimentary basins are characterized by low negative values. The pattern in the Bouguer gravity map exhibits mainly a Moho signature, with low negative values associated with a regional Moho deepening beneath the Sokoto Basin and the North Shield Belt. The pattern in the mantle gravity map exhibits a thermal signature of the lithospheric mantle. The high values (≥ 1000 mGal) of the mantle gravity disturbances detected over the Benin-Nigerian Block and the Phanerozoic cover of the West African Mobile Zone are possibly associated with a thermal signature of the lithospheric mantle. Another thermal signature of the lithospheric mantle along the Cameroon Volcanic Line partially outlines margins between the Oubanguides Neoproterozoic Belt and the southern extension of the West African Mobile Zone.